Conference Programme - Cooke, Pat (Irish Journal of Arts Management and Cultural Policy, 2015)
The Mapping an Altered Landscape: Cultural Policy and Management in Ireland conference took place on Wednesday 25th June 2014, 9-6pm, in the Fitzgerald Debating Chamber, University College, Dublin. The conference was designed as a series of short speaker presentations with significant time allocated for discussion and audience participation. There were 4 plenary sessions during the day that addressed issues of policy, structure and management practices and processes across the cultural field in Ireland, followed by a film screening. See also: www.culturalpolicyconference2014.ie. For further information or any of the transcripts detailed here, please contact: kerry.mccall@iadt.ie or pat.cooke@ucd.ie.